Macroalgal biomass subcritical hydrolysates for the production of polyhydroxyalkanoate (PHA) by Haloferax mediterranei. (January 2019) - Ghosh, Supratim; Gnaim, Rima; Greiserman, Semion; Fadeev, Ludmila; Gozin, Michael; Golberg, Alexander
Graphical abstract: Highlights: Macroalgae as carbon source for polyhydroxyalkanoate accumulation in Haloferax mediterranei. Utilization of Ulva sp. hydrolysate for PHA production with halophilic archaea. Application of extreme halophilic archaea for PHA production. Seagriculture for sustainable PHA production. Abstract: Non-conventional carbon sources, such as macroalgae, are sustainable alternatives for large-scale production of biopolymers. The present study examined macroalgae-derived carbohydrates, as carbon sources for the production of polyhydroxyalkanoates (PHAs) by Haloferax mediterranei . Simulants of the hydrolysates of seven different macroalgal biomasses were prepared and the PHA production was studied. A maximum biomass concentration with maximum PHA content was detected in medium prepared from green macroalgae. The highest cell dry weight and PHA concentrations were 3.8 ± 0.2 g·L −1 and 2.2 ± 0.12 g·L −1 respectively when Haloferax mediterranei was grown in 25% (w/w) of Ulva sp . hydrolysate, at 42 °C temperature and initial pH of 7.2. Poly(3-hydroxy-butyrate-co-3-hydroxyvalerate was the major PHA constituent. The present study demonstrated that Ulva sp. is a promising feedstock for PHA production.